2022
DOI: 10.1063/5.0078564
|View full text |Cite
|
Sign up to set email alerts
|

Impact of turbulence and secondary flow on the water surface in partially filled pipes

Abstract: Large eddy simulations (LESs) of turbulent flow in partially filled pipes at various filling degrees are conducted to investigate the response of the water surface to the turbulence and the secondary flow below it. LESs are validated first using experimental and direct numerical simulation data. At increasing water depth, the magnitude of water surface fluctuations increases with increasing strength of the main secondary flow. Visualizations of the instantaneous water surface and the turbulent flow underneath … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Furthermore, the maximum resultant secondary velocity varies from 1.7% to 2.13% of U max or from 1.92% to 2.44% of U , which agrees well with previous experimental and numerical results: Broglia et al (2003); Naot and Rodi (1982); Nezu and Nakagawa (1986); Nezu and Rodi (1985); Tominaga et al (1989) but is lower than the DNS values obtained by Nikitin (2021). Comparatively higher values are also reported in partial filled pipes (Brosda and Manhart, 2022;Liu et al, 2022aLiu et al, , 2022bNg et al, 2018). Interestingly, a decrease in the a r reduces the maximum normalized lateral velocity and the maximum normalized resultant secondary velocity for the tested rectangular channel flows.…”
Section: Casesupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the maximum resultant secondary velocity varies from 1.7% to 2.13% of U max or from 1.92% to 2.44% of U , which agrees well with previous experimental and numerical results: Broglia et al (2003); Naot and Rodi (1982); Nezu and Nakagawa (1986); Nezu and Rodi (1985); Tominaga et al (1989) but is lower than the DNS values obtained by Nikitin (2021). Comparatively higher values are also reported in partial filled pipes (Brosda and Manhart, 2022;Liu et al, 2022aLiu et al, , 2022bNg et al, 2018). Interestingly, a decrease in the a r reduces the maximum normalized lateral velocity and the maximum normalized resultant secondary velocity for the tested rectangular channel flows.…”
Section: Casesupporting
confidence: 91%
“…Broglia et al (2003), Grega et al (2002), Kang and Choi (2006), and Nikitin (2021) observed similar vortex in their LES (large-eddy simulation), experiments, RSM (Reynolds stress model), and DNS, respectively. These are also reported in partial filled pipes especially with 52% pipe filling (Brosda and Manhart, 2022;Liu et al, 2022aLiu et al, , 2022bNg et al, 2018;Wu et al, 2018). However, the bottom vortex is not found in those studies due to the absence of a solid corner between the walls.…”
Section: B Turbulence-driven Secondary Currents In Open Channelsmentioning
confidence: 76%
See 2 more Smart Citations
“…Large-eddy simulation (LES) method, using the code Hydro3D (Liu et al, 2022a(Liu et al, , 2022b, is applied in solving the filtered N-S equations for incompressible, unsteady and viscous flow:…”
Section: Transport Modelmentioning
confidence: 99%